Laser assisted self-assembly synthesis of porous hollow MoO3-x-doped MoS2 nanospheres sandwiched by graphene for flexible high-areal supercapacitors. (1st February 2020) - Li, Wei; Luo, Ting; Yang, Chao; Yang, Xiaopeng; Yang, Shuhua; Cao, Bingqiang
Abstract: Molybdenum disulphide (MoS2 ) with two-dimensional (2D) "graphene-like" stacked structure has attracted widespread attention as a type of novel energy storage materials because of its unique electronic properties. However, it suffers from fast capacity fading, low cycling stability and low specific capacitance for flexible devices. This study describes a facile and novel laser irradiation approach to fabricate self-assembled porous hollow MoO3-x -doped MoS2 nanospheres sandwiched by graphene for binder-free flexible supercapacitors (SCs). Due to the one-step laser-induced fragmentation and self-assembly of MoS2 nanoflakes with the photothermal reduction of graphene oxide (GO), the MoO3-x -doped MoS2 /graphene nanocomposites show enhanced conductivity, high surface area and increased electrochemical active sites for redox reactions. The symmetric flexible SCs deliver remarkable areal specific capacitance of 121.88 mF cm −2 under a current density of 0.6 mA cm −2, excellent cycle performance of almost no loss after 4000 cycles and high energy density of 73.4 μWh cm −2 under a power density of 240 μW cm −2 . This simple and ultra-fast laser-induced self-assembly technique could open up a new avenue towards high-performance flexible energy storage. Graphical abstract: Image 1